Analisis Potensi Ekowisata di Desa Sosor Dolok, Kecamatan Harian, Kabupaten Samosir (Analysis of Ecotourism Potential in Sosor Dolok Village, Harian Sub District, Samosir Regency) - Friska Silitonga; Siti Latifah; Yunus Afifuddin (Peronema Forestry Science Journal, 2013)
This research try to find out the ecotourism potential of Sosor Dolok Village toward the ecotourism development in Sosor Dolok Village. This research involves stakeholders such as residents of Sosor Dolok Village, the Department of Agriculture, the Department of Forest, and the Department of Tourism. The ecotourism potential identified by using the method of observation, discussion and interviews with stakeholders, and analyzed according to the scoring criteria in the analysis orientation of objects operating area and nature tourism attraction, Directorate General of Forest Protection and Nature Conservation 2003. The results of research showed that the natures potential are rice fields, coffee plantations, Sampuran Efrata Waterfall, mountain forests, and the Tower of Tele View. The ecotourism potential in that village are hiking, camping, and photo-hunting. Keywords: ecotourism, potential analysis, Sosor Dolok Village